2000
DOI: 10.1080/096392800413663
|View full text |Cite
|
Sign up to set email alerts
|

Innovation or renovation: effective project design for accounting and MBA students

Abstract: It has long been recognized that accounting and finance students need multidisciplinary skills and most degree courses reflect this in the curriculum. In addition, the growth of business administration courses, with a high accounting and finance content, and the constant call for relevance and 'real world' application, has persuaded many academics that educational progress can be made by employing project-based group work to bring together diverse skills and disciplines. This paper endorses that view, but sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In congruence with Davidson and Major's (2014) recommendation of gradually introducing more and more ill-structured problems, Collett (2000) suggests that live openended projects should only be conducted when students have considerable experience of simulated (fictional) less complex projects.…”
Section: Educational Activities Promoting Engagementmentioning
confidence: 81%
See 2 more Smart Citations
“…In congruence with Davidson and Major's (2014) recommendation of gradually introducing more and more ill-structured problems, Collett (2000) suggests that live openended projects should only be conducted when students have considerable experience of simulated (fictional) less complex projects.…”
Section: Educational Activities Promoting Engagementmentioning
confidence: 81%
“…Open-endedness is embedded in ill-structured as well as more structured problems. The idea is that students should investigate the issue from different angles and explore alternative solutions (Collett, 2000). This way, students learn that 'truth' and 'certainty' seldom exist in the real world (Karagiorgi and Symeou, 2005).…”
Section: Ill-structured and Open-ended Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hughes and Berry (2000) present a case study in which a qualitative research project was used to teach fundamentals of accounting research to graduate students. Collett (2000) describes the development of a merger and acquisitions group project over a 20-year period. The project is included in the second year of an MBA program at a UK university.…”
Section: Descriptive Articlesmentioning
confidence: 99%
“…Grablowsky and Rowell (1980), for instance, reported that almost 40% of the practitioners thought that business schools were lagging behind business practices, while only about 25% thought that business schools led business practices. Therefore, the calls for educators to broaden curricula had been loud during the 1980s and 1990s, as business schools were being criticized for graduating students deficient in critical skills (e.g., Accounting Education Change Commission, 1990;Adler and Milne;Collett, 2000;International Federation of Accountants, 1996;Nabi, 2003). In a world of globalization and competition, on the other hand, different professional and accrediting bodies produce guidelines for building coherent business programs with expectations for cognitive and behavioral skills, leading to global citizens (Barrie, 2004;Bowden & Merton, 1998, Kavanagh & Drennan, 2008.…”
mentioning
confidence: 99%